Políticas de ação afirmativa e o direito fundamental à igualdade: o sistema de cotas raciais para o ingresso dos negros no ensino superior brasileiro - Belisário, Bethânia Silva (2007)
Seeks to analyse the adoption of the politics of racial quotas for black persons with the end of entry in the Brazilian higher education, under the perspective of the principle of the equality. Through a deductive approach and bibliographical research, it works the following problematic: does the adoption of the politics of racial quotas for black persons, aiming for the entry the Brazilian higher education, infringe the principle of the equality? It admits the hypothesis of which the adoption brings infringement to the above mentioned principle. It structures the theme in three chapters: in the first chapter, it emphasizes the principle of the equality revealing it in his traditional formal and material aspects, and in the innovatory faces of the equality of opportunities and results, appeared with the aim of making the material equality real, especially in what concerns obligatoriness of differentiation of treatment. In the second chapter, focuses the differentiated treatment through the affirmative action politics adoption treating them, for so much, in the general issues of its concept, development, justification, the forms of implementation and objectives. In the third chapter, it analyses the adoption of the system of racial quotas for the entry of black persons in the Brazilian higher education, on basis of the chosen factor of discrimination, in the logical correlation between him and the differentiated treatment offered - correlation focused under the exam of the triad of the - and, in the consonance with the precepts of the Federal Constitution, aiming to notice if his adoption brings or not insult to the principle of the equality. It confirms the initial hypothesis, concluding: a) it is unjustified the choice of the race as criterion of discrimination b) there is not logical correlation between the chosen criteria for the adoption of the measure and the difference of handling adopted, therefore, although adequate, they are unnecessary and disproportionate in strict sense c) there is no consonance with the constitutional precept related to the individual merit.